Modern political systems : Europe - Macridis, Roy C. (New Jersey : Prentice-Hall, 1987)
This edition deals with the key concepts that guide students to study political systems and to make comparisons.
I. Introduction -- II. Politics of great britain -- III. Politics of france -- IV. The federal republic of germany - west germany -- V. Scandinavia: The politics of stability -- VI. Mediterranean europe: toward an end to instability? -- VII. The european economic community: Political and economic union -- VIII. Soviet politics -- IX. Politics in communist eastern europe.
Includes index.
Keywords: POLITICAL SCIENCE